Comment on "Evaluation on the interaction between Chinese traditional philosophical culture and higher education ideas" - Cheng, Liu (2024)
Commented article: ZHANG, Y. Evaluation on the interaction between Chinese traditional philosophical culture and higher education Ideas. Trans/Form/Ação: Unesp journal of philosophy, v. 47, n. 4, e0240055, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14625.